Đặt x - 2017 = a
Phương trình trên tương đương:
\(\dfrac{\left(-a\right)^2-\left(-a\right)\left(a-1\right)+\left(a-1\right)^2}{\left(-a\right)^2+\left(-a\right)\left(a-1\right)+\left(a-1\right)^2}=\dfrac{5}{3}\)
\(\Leftrightarrow\dfrac{a^2+a^2-a+a^2-2a+1}{a^2-a^2+a+a^2-2a+1}=\dfrac{5}{3}\)
\(\Leftrightarrow\dfrac{3a^2-3a+1}{a^2-a+1}=\dfrac{5}{3}\)
\(\Leftrightarrow9x^2-9x+3=5x^2-5x+5\)
\(\Leftrightarrow4x^2-4x-2=0\)
\(\Leftrightarrow\left(x-\dfrac{1+\sqrt{3}}{2}\right)\left(x-\dfrac{1-\sqrt{3}}{2}\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}\dfrac{1+\sqrt{3}}{2}\\\dfrac{1-\sqrt{3}}{2}\end{matrix}\right.\)
Vậy tập nghiệm của phương trình: \(S=\left\{\dfrac{1+\sqrt{3}}{2};\dfrac{1-\sqrt{3}}{2}\right\}\)